PENGARUH KOMPETENSI DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA DOSEN DIMODERASI BUDAYA ORGANISASIONAL ( Studi pada Perguruan Tinggi Maritim di Semarang ) - Anwar, Amthori; Liana, lie (Jurnal Ilmiah Telaah Manajemen, 2016)
This study aimed to analyze the effect of competence and organizational commitment moderated organizational culture in improving the performance of the maritime college lecturer. This research is located in the city of Semarang In this study population of 177, while the samples taken a number of 123 respondents, using probability random sampling. Measurements using a Likert scale of 5 (seven) answer. Alternative instruments test used are validity and reliability, while the test model used is the coefficient of determination (R Adjsuted Square), test F (Goodness of Fit). Hypothesis test used in this study used regression analysis. Testing the hypothesis used t test frequency distribution of the level of significance (α) of 5%. The results showed the coefficient of determination (Adjusted R Square) 0.450, meaning that the independent variables (organizational culture, competencies and organizational commitment) to give effect to 45% in dependent variable (performance lecturers). The remaining 55% influenced by other variables not included in the study. Based on the research results summarized as follows; Competence does not affect the performance of lecturers, Commitment Organizational does not affect the performance of lecturers, Cultural Organisation positive and significant effect on the performance of lecturers, organizational culture does not moderate the effect of competence on the performance of lecturers, organizational culture does not moderate the influence of organizational commitment to the performance of lecturers Keywords:Performance, Competence, Organizational Commitment, Organizational Culture, Moderation